Identifikasi Bahaya dan Penilaian Risiko Kebakaran dengan Metode Fire Risk Assessment pada PT Aneka Gas Industri Tbk, Bekasi - Agustina, Agustina; Pramesti, Regina Intan (STIKes Persada Husada Indonesia, 2021)
Hazard identification process is one part of risk management. Risk assessment is a process to determine the priority of control over the level of risk of accidents or occupational diseases. Hazard identification process can be started by group. Fire Risk Assessment (FRA) is a process for describing risks associated with fires discussing the fire scenario or scenarios of concern, their probabilities, and potential consequences. The purpose of this study was to determine